The association of liver enzymes with diabetes mellitus risk in different obesity subgroups: A population-based study - Zheng, Dinghao; Zhang, Xiaoyun; You, Lili; Li, Feng; Lin, Diaozhu; Sun, Kan; Ren, Meng; Yan, Li; Wang, Wei (Frontiers in Endocrinology, 2022)
Background Numerous observational studies have shown that liver enzymes correlated with diabetes mellitus (DM) risk significantly, but limited studies showed whether different obesity subgroups present the same correlation. Our objective was to evaluate the association of liver enzymes with DM risk in different obesity subgroups based on a middle-aged Chinese population. Methods We conducted a population-based cross-sectional study and surveyed 9,916 people aged 40 years and above. A two-slope linear regression model was used to analyze the cutoff points of obesity in DM risk. Restricted cubic splines were used to analyze the correlation between liver enzymes and DM risk in different obesity categories. The odds ratios and 95% confidence intervals (CIs) were calculated using the logistic regression model. Results The cutoff points of body mass index (BMI) and waist circumference were 30.55 kg/m2 and 98.99 cm for DM risk, respectively. The serum gamma-glutamyl transferase (GGT) concentration was positively correlated with DM risk in the subgroups with waist circumference <98.99 cm [OR = 1.04, 95% CI (1.03–1.05)], BMI <30.55 kg/m2 [OR = 1.04, 95% CI (1.03–1.05)], and BMI ≥30.55 kg/m2 [OR = 1.18, 95% CI (1.04–1.39)], but not in the subgroup with waist circumference ≥98.99 cm. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) concentrations have no significant correlation with the risk of diabetes in all groups. Conclusion The results showed that serum GGT concentration was correlated with DM risk but not with AST or ALT in the middle-aged population. However, the correlation disappeared when waist circumference was over 98.99 cm, and serum GGT concentration had a limited value for DM risk in waist circumference over 98.99 cm.